Answer:
The starting velocity.
Step-by-step explanation:
We must understand that this equation comes from the following equation of kinematics.
![v_(f)=v_(o)+a*t](https://img.qammunity.org/2022/formulas/physics/high-school/sv8rgzar5pxp99z732sb953u8c8zyc4ycn.png)
where:
Vf = final velocity = 33 [m/s]
Vo = starting velocity [m/s]
a = acceleration = 3 [m/s²]
t = time = 30 [s]
So, these values can be assembly in the following way:
![v_(f)=v_(o)+a*t\\a*t=v_(f)-v_(o)\\3=(33-v_(o))/(30)](https://img.qammunity.org/2022/formulas/physics/college/zb9i9ymj29ov9khfh1uk1uwkbmohmxygkq.png)